2010
DOI: 10.3390/mca15030439
|View full text |Cite
|
Sign up to set email alerts
|

On Some Double Lacunary Sequence Spaces of Fuzzy Numbers

Abstract: Abstract. In this paper we introduce a new concept for lacunary strong P-convergent with respect to an Orlicz function and examine some properties of the resulting sequence space of fuzzy numbers. We also show that if a sequence is lacunary strong Pconvergence with respect to an Orlicz function then it is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Tripathy and Sarma [11] proposed certain double sequence spaces of fuzzy real numbers defined by the Orlicz function in 2011 in order to investigate their various features. In 2010, Savas [12] used the Orlicz function to develop a novel concept for double lacunary sequence spaces of fuzzy numbers and investigate whether a sequence of fuzzy numbers is double strongly P-convergent with respect to an Orlicz function. Kılınç, G., and Solak, İ.…”
Section: Introductionmentioning
confidence: 99%
“…Tripathy and Sarma [11] proposed certain double sequence spaces of fuzzy real numbers defined by the Orlicz function in 2011 in order to investigate their various features. In 2010, Savas [12] used the Orlicz function to develop a novel concept for double lacunary sequence spaces of fuzzy numbers and investigate whether a sequence of fuzzy numbers is double strongly P-convergent with respect to an Orlicz function. Kılınç, G., and Solak, İ.…”
Section: Introductionmentioning
confidence: 99%
“…Savas [21] introduced and discussed double convergent sequences of fuzzy numbers and showed that the set of all double convergent sequences of fuzzy numbers is complete. Different classes of sequences of fuzzy real numbers have been discussed by 28,[30][31][32]38]), Savas and Mursaleen [42] and B.C. Tripaty and B. Sarma [47] B.C.…”
Section: Introductionmentioning
confidence: 99%
“…The credit goes to Kumar et al [17] who first defined I-convergence for sequences of fuzzy numbers. For an extensive view of this subject, we refer [2,5,10,11,12,13,16,23].…”
Section: Introductionmentioning
confidence: 99%